Lissos in Illyria: Two Centuries of Hellenistic Pottery, and a Plea for the Publication of Contextual Material - Kögler, Patricia (Journal of Hellenistic Pottery and Material Culture, 2019)
In 1934, Homer A. Thompson published a first, brief typology and chronology of Athenian Hellenistic pottery in order »to clarify and amplify that chapter in the ceramic history of Athens which covers the time between the end of the fourth and the end of the second century B.C.« The basis of his investigation were five well-stratified, large assemblages of Hellenistic table and cooking ware from the Athenian Agora. Offering the opportunity to anchor assemblages of similar types in them and to construct a wide chronological net, these groups (A–E) soon gained importance for sites in the entire Mediterranean. Now, 85 years after their publication and with later revisions, neither the groups A–E nor Thompson’s publication have lost their meaning. For good reasons: First, the significance of pottery assemblages like Thompson’s groups goes far beyond the chronological aspects to which they are often reduced. And second, ›Two Centuriers of Hellenistic Pottery‹ demonstrates methodically clear all steps that lead to the determination of production times and development stages of individual vessel types and also makes it understandable for other colleagues who have no direct access to the Athenian material. Last but not least, the thorough documentation and publication of the underlying contextual material offers the opportunity to reevaluate it even decades later – and thus also to specify the chronological data according to the expanded state of knowledge.